Evaluation of an intervention program to promote neck care for computer user among staff and students of a Malaysian public university - Ahmad Sharoni, Siti Khuzaimah; Ismail, Suriani; P., Alagirisamy; Zulkifley, Nuraisyah Hani; Amin, S.; S., Shahla (Community Health Society Malaysia, 2016)
Background: Computers are one of the most useful equipment developed in this electronic era. However incorrect posture and prolonged use of computers are risk factors for developing neck pain. A health promotion program was developed to educate computer users regarding neck care. The program was then evaluated to observe its effects in increasing knowledge, attitude and practice among the respondents. Materials and Methods: This was an intervention study conducted in a local public university. A set of materials consisting of a pamphlet, posters and questionnaire, were developed for the study. The pamphlet and posters were based on a study on exercises performed while sitting, while the questionnaire was based on a study assessing a neck care intervention program. The materials were assessed and validated prior to the program. Study variables were respondents’ characteristics, knowledge, attitude and practice/intention to practice neck care. The knowledge, attitude and practice/intention to practice were measured at baseline and post intervention and the changes were compared. Result: A total of 41 respondents participated. At baseline, only 61% of the respondents knew that daily computer use for 2 hours or more increased the risk of developing neck problem, however the percentage increased significantly after the program (P=0.001). The attitude toward the necessity to do exercise while working in front of the computer was 85.5% at the beginning but had also increased significantly after the program (P=0.008). All parameters forming the intention to practice good neck care (i.e. to sit with straight upper back, to do simple neck exercise while working in front of the computer and to adjust sitting position to maintain good posture) were significantly increased (P<0.05) after the intervention program. Conclusion: The knowledge and attitude regarding good neck care and the intention to practice good neck care significantly improved after the intervention program. More intervention programs to promote neck care for computer users should be carried out.